2002
DOI: 10.1074/jbc.m108563200
|View full text |Cite
|
Sign up to set email alerts
|

The Biologically Crucial C Terminus of Cholecystokinin and the Non-peptide Agonist SR-146,131 Share a Common Binding Site in the Human CCK1 Receptor

Abstract: The cholecystokinin (CCK) receptor-1 (CCK1R) is a G protein-coupled receptor, which mediates important central and peripheral cholecystokinin actions. Our aim was to progress in mapping of the CCK1R binding site by identifying residues that interact with the methionine and phenylalanine residues of the C-terminal moiety of CCK because these are crucial for its binding and These new and important insights will serve to better understand the activation process of CCK1R and to design or optimize ligands.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
105
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(109 citation statements)
references
References 39 publications
2
105
1
Order By: Relevance
“…Likewise, isoleucine in TM3 of the melanocortin-4 receptor was important for high affinity for melanocortin-4 receptor ligands (tetrahydroisoquinoline, M10, and adrenocorticotropin hormone) (Nickolls et al, 2003). Our results are similar to findings with both the CCK-1 and NK-2 receptors, where replacement of isoleucine in TM5 or TM7, respectively, with alanine markedly decreased agonist affinity (Greenfeder et al, 1999;Escrieut et al, 2002). There is almost no information on the molecular mechanisms that determine the importance of the presence of an isoleucine in the different Gprotein-coupled receptors for high-affinity ligand interaction.…”
Section: Tablesupporting
confidence: 85%
See 1 more Smart Citation
“…Likewise, isoleucine in TM3 of the melanocortin-4 receptor was important for high affinity for melanocortin-4 receptor ligands (tetrahydroisoquinoline, M10, and adrenocorticotropin hormone) (Nickolls et al, 2003). Our results are similar to findings with both the CCK-1 and NK-2 receptors, where replacement of isoleucine in TM5 or TM7, respectively, with alanine markedly decreased agonist affinity (Greenfeder et al, 1999;Escrieut et al, 2002). There is almost no information on the molecular mechanisms that determine the importance of the presence of an isoleucine in the different Gprotein-coupled receptors for high-affinity ligand interaction.…”
Section: Tablesupporting
confidence: 85%
“…However, when isoleucine 199 was substituted by amino acids with high hydrophobicity (leucine and valine) or with a moderately high hydrophobicity (methionine), either no difference or only a slight decrease in the affinity of NMB for NMBR was observed. These results support the conclusion that the hydrophobicity of the substitution in position 199 of NMBR plays a crucial role for NMBR affinity for NMB and suggest that the substitution of isoleucine with alanine creates a difference in the transfer-free energies that could influence hydrophobicity and the thermodynamics of protein folding (Escrieut et al, 2002).…”
Section: Tablesupporting
confidence: 84%
“…The NH 2 -terminal moiety of CCK is tightly linked to extracellular residues of CCK1R, including residues in the second extracellular loop at the top of transmembrane (TM) helix I and within the third extracellular loop (16,237). The COOH-terminal tetrapeptide of CCK appears to be embedded between TM helices III, V, VI, and VII through a network of both ionic and hydrophobic interactions (16,145,168). This binding mode of the COOH terminus of CCK into CCK1R is in agreement with an NMR study of the interactions between CCK and a fragment of CCK1R comprising the top portion of helix VI and the third extracellular loop as well as a fragment including amino acids at the top of transmembrane segment I (173, 373).…”
Section: A Localization Of Ligand Binding Sitesmentioning
confidence: 99%
“…Several critical contacts between the CCK1R binding site and CCK were successively discovered: Met195 and Arg197 located in the second extracellular loop, were shown to interact with the sulfated tyrosine (Gigoux et al 1998(Gigoux et al & 1999b; Arg336 and Asn333 at the top of helix VI were demonstrated to pair with the Asp carboxylate and the Cterminal amide of CCK, respectively (Gigoux et al 1999a). More recently, search for residues of the receptor in interaction with Met/Nle and Phe of CCK led to description of a network of hydrophobic residues including Cys94, Met121, Val125, Phe218, Ile329, Phe330, Trp326, Ile352, Leu356 and Tyr360 all involved in the binding site for CCK and in the activation process of the CCK1R (Escrieut et al 2002) (fig. 2).…”
Section: Mapping Of Cck1r Binding Site For Cckmentioning
confidence: 99%
“…Therefore, side-chains of Met121 of CCK1R and Met of CCK are not directly involved in the activation process but the ''hydrophobic weight'' near position 121 is crucial for CCK1R activation. Application of dynamic procedures on the model of the CCK1R.CCK complex yielded the very exciting result that introduction of hydrophobic residues near position 121 determines positioning of the aromatic ring of the Phe of CCK within the binding pocket (Escrieut et al 2002). Obviously, this modelling result needs experimental verification.…”
Section: First Structural Data On the Mechanism Of Activation/ Inactimentioning
confidence: 99%